(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Conventional orthognathic surgery sometimes fails to achieve optimal aesthetic results in Class III malocclusion patients with a low occlusal plane angle. Clockwise rotation of the Maxillo-Mandibular Complex (MMC) has been implemented to address aesthetic limitations in these cases. However, existing evidence primarily focuses on isolated patient groups and remains limited in Vietnam. Objective: To evaluate the changes in hard and soft tissues following clockwise MMC rotation surgery in the treatment of Class III skeletal malocclusion. Materials and Methods: A retrospective longitudinal descriptive study was conducted on 30 patients (9 males, 21 females; mean age 25) diagnosed with Class III skeletal malocclusion who underwent preoperative orthodontics and clockwise MMC rotation surgery. Cephalometric measurements were performed at three stages: preoperative (T1), one week postoperative (T2), and six months postoperative (T3). Hard tissue changes were assessed using T2–T1, while soft tissue changes were evaluated via T3–T1. Results: Postoperatively, skeletal parameters showed statistically significant changes (p < 0.05) the ANB angle increased, achieving a Skeletal Class I relationship; the mandibular plane angle (MP-SN) increased, reflecting a downward and backward rotation of the mandible. Regarding soft tissues, the nasolabial angle and facial contour angle increased significantly, resulting in a more harmonious facial profile. Conclusion: Clockwise rotation of the maxillo-mandibular complex is an effective method for treating Class III malocclusion. It significantly improves facial profile aesthetics by increasing maxillary incisor display and midface prominence.